1977
DOI: 10.1017/s0022029900020458
|View full text |Cite
|
Sign up to set email alerts
|

The oxidation of lipids by components of bovine milk-fat globule membrane

Abstract: SummaryBovine milk-fat globule membrane was solubilized with a zwitterionic surfactant and subjected to chromatography on agarose, with the surfactant in the eluant. Fractions were tested for their effects on the oxidation of buffered linoleate. The maximum oxidative capability was greatly enhanced by the addition of Cu, and became associated with the phospholipids.Further chromatography of the retarded protein peak from agarose on Sephadex G-200, again in the presence of surfactant, gave 2 protein peaks. Oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1981
1981
2004
2004

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…The prooxidant effect of the milk fat globule membrane has been attributed to trace metals, notably iron and copper, associated with membrane proteins. Lipid oxidation in milk may also be related to the oxidative susceptibility of the polyunsaturated phospholipids present in these membranes [32,33]. The antioxidative properties of the milk components have been mainly attributed to the casein and citric acid, which are recognised efficient metal chelators [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…The prooxidant effect of the milk fat globule membrane has been attributed to trace metals, notably iron and copper, associated with membrane proteins. Lipid oxidation in milk may also be related to the oxidative susceptibility of the polyunsaturated phospholipids present in these membranes [32,33]. The antioxidative properties of the milk components have been mainly attributed to the casein and citric acid, which are recognised efficient metal chelators [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…The latter phenomenon may contribute to the oxidation of unsaturated fatty acids of membrane phospholipids (McPherson & Kitchen, 1983; van Boekel & Walstra, 1995). This appears to be so particularly for phosphatidyl ethanolamine, which contains 40-60% unsaturated fatty acids, of which about one-third is polyunsaturated, and which strongly binds copper (Allen & Humphries, 1977;Deeth, 1997). Oxidation of MFGM constituents may thus be expected to affect the fluidity and stability of the MFGM.…”
Section: Temperature and Ageingmentioning
confidence: 99%
“…Second, there is another influencing factor that should be responsible for that behavior and this could be the presence of the enzyme xanthine oxidase in a great extent. It has been found that xanthine oxidase for MFGM has a prooxidative role and also that the oxidative capabilities of this enzyme were greatly enhanced by heat denaturation (Allen and Humphries 1977;Bruder 1980). Allen and Humphries postulated that this may have been caused by release of bound nonactive Cu or more probably by an increased exposure of metal containing prostetic groups following denaturation.…”
Section: Discussionmentioning
confidence: 99%
“…Specific involvement of xanthine oxidase in lipid peroxidation has been demonstrated by Allen and Humphries (1977). Therefore, knowing the important role of this enzyme in the development of lipid oxidation, the MFGM enzyme activity was studied.…”
Section: Xanthine-oxidase Activitymentioning
confidence: 99%